Analysis of The Effectiveness of Using Lightweight Materials on Embankments Over Soft Soil (Case Study: Betung Toll Road (SP Sekayu) –Tempino - Jambi Section 1B) - Teguh Sakti Muttaqin; Ria Asih Aryani Soemitro; Trihanyndio Rendy Satrya (Interdisciplinary Social Studies, 2025)
The construction of the Betung (SP Sekayu) – Tempino – Jambi Trans Sumatra Toll Road Section 1B, particularly at STA 55+900, faces significant geotechnical challenges due to soft subgrade in the floodplain area. Geotechnical investigations indicate that the surface layer up to a depth of 4.45 meters is dominated by very soft silty clay with an N-SPT value of 2-4, which risks triggering embankment instability and excessive settlement in the planned 6.6-meter high embankment. This study aims to analyze the effectiveness of lightweight fill material in the form of foam mortar as a substitute for conventional embankment materials. Numerical analysis based on the finite element method (Plaxis 2D) was carried out by modeling variations in foam mortar thickness of 25%, 50%, and 75% of the embankment height. The simulation results show that the use of lightweight materials effectively increases stability and reduces settlement. The most optimal design configuration was obtained at a substitution variation of 75% foam mortar, which resulted in a Safety Factor (SF) value of 2.727. This value indicates an 58.64% increase in stability compared to conventional soil embankments and is capable of reducing total settlement by up to 25.26% (by 9.745 cm). These findings recommend foam mortar as an alternative solution that meets the technical criteria for stability and deformation.